BAHAYA INFEKSI HIV (BUMAN IMMUNODEFICIENCY VIRUS) BESERTA ALTERNATIF PEMECAHANNYA - Senam, Senam (Jurnal Cakrawala Pendidikan, 2016)
The virus called HIV can infect human cells and cause the disease called AIDS. HIV infection is principally the integration between the DNA of the HIV and that of the host cell so that the DNA of the HIV undergoes replication at the time the host cell undergoes fission. The HIV is unable to conduct a metabolism process without any host cell. In order to survive, the HIV makes use of the energy, precursor molecules, and essential enzymes of the host cell. The competition occurring between the HIV and the host cell will result in the host cell's growth b,eing disturbed. Human cells whch can be infected by the HIV include the T helper lymphocyte cells, the macrophage cells, and the dendritic cells. The T helper lymphocyte cells play a part in the biosynthetic process of antibodies. The macrophage cells are very useful in the protection of cells from infection caused by a number of pathogenous microorganisms as well as toxic chemical substances. The dendritic cells function as the cells providing antigens as well as the cells complementingthe T cytotoxic cells. The three types of cells above are responsible for the body's immunity system. The occurrence of H V -infection on these cells causes a decline in the human body's immunity system and results in AIDS. The contagon of HIV can happen via sexual intercourse (heterosexual or homosexual), blood transfusion, the use of the same needle for injections to different persons, and saliva. Prevention of HTV infection can be done by avoiding the behaviors described above whle for curative treatment can possibly be done by gving antibiotics which can hinder the biosynthetic process of the reverse transcriptase enzyme protein and decrease the activity of the enzymes playing a part in the modification process of a foreign DNA. In social life, ostracism on the IW carrier is not approved because the conta- @on of ttus virus is not via air, the slun, or clothes.